Morphologic and morphometric differences between gullies formed in different substrates on Mars: new insights into the gully formation processes - R. K. Sinha; R. K. Sinha; D. Ray; T. De Haas; S. J. Conway; A. Noblet (Earth Surface Dynamics, 2023)
Martian gullies are kilometer-scale, geologically young features with a source alcove, transportation channel, and depositional fan. On the walls of impact craters, these gullies typically incise into bedrock or surfaces modified by the latitude-dependent mantle (LDM; inferred as consisting of ice and admixed dust) and glaciation. To better understand the differences in the alcoves and fans of gullies formed in different substrates and infer the flow types that led to their formation, we have analyzed the morphology and morphometry of 167 gully systems in 29 craters distributed between 30 and 75∘ S. Specifically we measured length, width, gradient, area, relief, and relief ratio of the gully alcoves and fans; Melton ratio, relative concavity index, and perimeter; and form factor, elongation ratio, and circularity ratio of the gully alcoves. Our study reveals that gully alcoves formed in LDM/glacial deposits are more elongated than the gully alcoves formed in bedrock, and they possess a distinctive V-shaped cross section. We have found that the mean gradient of fans formed by gullies sourced in bedrock is steeper than the mean gradient of fans of gullies sourced in LDM/glacial deposits. These differences between gullies were found to be statistically significant and discriminant analysis has confirmed that alcove perimeter, alcove relief, and fan gradient are the most important variables for differentiating gullies according to their source substrates. The comparison between the Melton ratio, alcove length, and fan gradient of Martian and terrestrial gullies reveals that Martian gully systems were likely formed by terrestrial debris-flow-like processes. Present-day sublimation of CO2 ice on Mars may have provided the adequate flow fluidization for the formation of deposits akin to terrestrial debris-flow-like deposits.